O estudo dos gestos vocais e corporais no telejornalismo brasileiro - Cotes, Claudia Simone Godoy (2008)
This recearch aims to analyse the relation between vocal and body gestures in the speech of TV newscasters, as well as to investigate the changes, in stylistic terms, that have taken place in this genre, by interpreting it in light of the specificities of its social-historic moment. Three historic moments will be considered: the initial moment of TV newscasting (1968), the intermediary moment (1980) and the present moment (2005). The term vocal gesture is used herewith to define the elements of vocal dynamics and vocal quality, that is, those elements which constitute the prosody of the languages and their interaction with the phonic segments. The term body gesture is used to refer to the bodily movements connected to vocal expression. The analysis of vocal gestures is anchored in Experimental Phonetics and the analysis of body gestures is based on communicative approaches of kinesthetic nature. The methodological procedures of data analysis involve the extraction of the acoustic parameters of duration and f0 of phonic segments, syllables and GNPC. The analysis of body gestures involved capturing vídeo images which show sequences of postural movements of the hands and face. The presence or absence of concomitant vocal and body gestures is analysed in relation to the placement of prominence and pauses by TV newscasters. This study points to stylistic changes in the format of TV newscasting over the last decades. Such evolution reflects the tendency towards shifting from a reading style heavily influenced by the spelling of words and minimized bodily gestuality to a more expressive style of oral narration of facts. This tendency may be interpreted as a reflex of the media´s effort to establish a connection with its viewers